2005
DOI: 10.1080/13880200590951658
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antifungal Compounds fromFerula persica. var.persica.

Abstract: In this investigation, the antifungal activities of chloroform and water extracts of Ferula persica. var. persica. Willd. roots were studied using conventional disk diffusion method. The chloroform extract showed antifungal activity at concentrations tested. Bioassay-guided fractionation study of the chloroform extract by preparative thin-layer chromatography (PTLC) detected two antifungal fractions that were effective against some fungi. Using conventional spectroscopy methods, the active fractions were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…persica Willd. (extracts) (35), F. kuhistanica Korovin (fruit extract) (36) and F. communis Linn. (sesquiterpenes from rhizomes) have been reported (37).…”
Section: Resultsmentioning
confidence: 99%
“…persica Willd. (extracts) (35), F. kuhistanica Korovin (fruit extract) (36) and F. communis Linn. (sesquiterpenes from rhizomes) have been reported (37).…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial activity of the essential oil and plant extracts of S. gracilis has not been studied up to now. However, it was previously reported that the essential oil or extracts of some members of the Apiaceae family, such as Ferula gummusa, Hippomarathrum microcarpum and Ferula persica (Eftekhar, Yousefzadi, & Borhani, 2004;Mirjani, Shahverdi, Iranshahi, Amin, & Shafiee, 2005;Ozer et al, 2007), had antimicrobial activity.…”
Section: Antimicrobial Activitymentioning
confidence: 98%
“…Numerous reports have demonstrated that plant products possess a variety of in vitro antioxidant properties and that the consumption of food or beverages rich in antioxidant phytochemicals resulted in positive effects on human health and on the aging process [8], [9]. It has been shown that PSA has antifungal activity [10]. It has also been reported to inhibit matrix metalloproteinase activity [11].…”
mentioning
confidence: 99%